A Study of Platinum Group Metals in Three-Way Autocatalysts. Issue 4 (1st October 2013) - Cooper, Jonathan; Beecham, Joel
The price differential between platinum and palladium has driven the industry to adopt emissions control catalyst formulations for gasoline engines that contain higher levels of Pd than Pt, and in most cases no Pt. In addition fluctuations in the price of rhodium have led to thrifting of this metal. This study compares the performance of ten different catalyst compositions with varying ratios of Pt, Pd and Rh for a Euro 5 vehicle and under bench test conditions. The results show that a system with low Rh loading can readily be improved by increasing the Rh loading and there is a relatively large effect of doing this by a small amount. Increasing the Pd or Pt loading also improves emissions performance but by a significantly smaller amount than the effect of changing the Rh loading. Conversely it may be possible to decrease the Pt or Pd loading with only a small effect on emissions. Furthermore it was found that Pd outperforms Pt under most conditions, although not significantly. The difference appears greater under more stressful conditions such as high-speed driving or wide perturbation amplitude.